The Impact of Specific Language Impairment (SLI) in 6-Year-Old Children - Daulay, Sholihatul Hamidah; Niswa, Khairun; Pratiwi, Tara; Khairunnisa (Universitas Nahdlatul Ulama Surabaya, 2022)
This study focuses on the discipline of psycholinguistics regarding language disordersin children, to be precise of Specific Language Impairment (SLI). This article analyzestwo 6-year-old children who show the characteristics of having SLI in languagedisorders during the COVID-19 pandemic. In order to carry out this study, theresearcher used a qualitative descriptive research method. The method aims to describein a systematic, actual, and accurate way. This research is an analytical study of officialdocuments such as books, articles, journals, and the internet. The accuracy of the data isobtained from the observations of the researcher herself. This study reports that childrenwith SLI often stay until school age and can lead to a lack of academic ability and causevarious psychosocial problems. Some of the causes of SLI in children include genetic,environmental, and social factors, pre and perinatal, gender, prematurity, weight, socio-economic status, maternal mental status, mother's education, and vocabulary, and history of speech-language difficulties.